2007
DOI: 10.1088/0967-3334/28/8/003
|View full text |Cite
|
Sign up to set email alerts
|

Muscle tone in different joint positions and at submaximal isometric torque levels

Abstract: The aim was to evaluate the tone and electric activity of the quadriceps muscle at rest and different torque levels. The second aim was to study whether thickness of soft tissues and change in the joint position would affect muscle tone. Eighteen healthy subjects participated. Computerized muscle tonometer (CMT) and surface electromyography (sEMG) measurements were performed: seated, first at rest with leg straight and then with the knee at 60 degrees . Thereafter measurements were obtained at levels of 80, 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…This study is in keeping with previous studies reporting that muscle compliance (tissue displacement) measurements performed perpendicularly to the tissue are sensitive to changes in muscle activation levels (1,2,11,14,20). Alamaki et al (1) found that when muscle torque increased from 0 to 80% of MVC, the compliance decreased by 48%, and the torque and compliance correlated significantly (r = 20.67, p , 0.001). In this study, the change from 0 to 80% of MVC was even larger, 66%.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This study is in keeping with previous studies reporting that muscle compliance (tissue displacement) measurements performed perpendicularly to the tissue are sensitive to changes in muscle activation levels (1,2,11,14,20). Alamaki et al (1) found that when muscle torque increased from 0 to 80% of MVC, the compliance decreased by 48%, and the torque and compliance correlated significantly (r = 20.67, p , 0.001). In this study, the change from 0 to 80% of MVC was even larger, 66%.…”
Section: Discussionsupporting
confidence: 91%
“…Many factors affect the level of muscle tone, such as muscle structure (9,17,29) intramuscular pressure (17), pain (39), temperature (18,27), preceding rest or exercise (28,34), diseases (19,25,31,32), and medication (30,35). During contraction the muscle tone changes depending on level of force production, muscle length, and speed of contraction (1,5,8,26).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although muscle hardness may be associated with muscle tone or stiVness, the deWnition of these terms has been ambiguous. Muscle tone and stiVness has been deWned as the ratio of change in force to change in length along the muscle's long axis (Alamaki et al 2007;Leonard et al 2004). On the other hand, muscle hardness, which is detectable by palpation, can be simply deWned as the resistance oVered by the muscle against perpendicular pressure (Horikawa et al 1993;Murayama et al 2000Murayama et al , 2005.…”
Section: Introductionmentioning
confidence: 99%